AST to Platelet Ratio Index Predicts Mortality in Hospitalized Patients With Hepatitis B-Related Decompensated Cirrhosis. Issue 9 (March 2016) - Mao, Weilin; Sun, Qinqin; Fan, Jian; Lin, Sha; Ye, Bo
Abstract : Abstract: Aspartate aminotransferase to platelet ratio index (APRI) has originally been considered as a noninvasive marker for detecting hepatic fibrosis in patients with chronic hepatitis B and C. APRI has been used for predicting liver-related mortality in patients with chronic hepatitis C virus infection or alcoholic liver disease. However, whether APRI could be useful for predicting mortality in chronic hepatitis B virus (HBV) infection remains unevaluated. This study aims to address this knowledge gap. A total of 193 hospitalized chronic HBV-infected patients (cirrhosis, n = 100; noncirrhosis, n = 93) and 88 healthy subjects were retrospectively enrolled. All patients were followed up for 4 months. Mortality that occurred within 90 days of hospital stay was compared among patients with different APRI. APRI predictive value was evaluated by univariate and multivariate regression embedded in a Cox proportional hazards model. APRI varied significantly in our cohort (range, 0.16–10.00). Elevated APRI was associated with increased severity of liver disease and 3-month mortality in hospitalized patients with HBV-related cirrhosis. Multivariate analysis demonstrated that APRI (odds ratio: 1.456, P  < 0.001) and the model for end-stage liver disease score (odds ratio: 1.194, P  < 0.001) were 2 independent markers for predicting mortality. APRI is a simple marker that may serve as an additional predictor of 3-month mortality in hospitalized patients with HBV-related decompensated cirrhosis.